Shaping forces modelling genetic variation patterns in the naturally fragmented forests of a South-American Beech - Azpilicueta, Maria Marta; Gallo, Leonardo Ariel (Elsevier, 2023)
Fourteen natural populations of the South-American Beech Nothofagus obliqua at the Eastern naturally fragmented area of its distribution range were subjected to genetic analysis using genetic markers. The genetic characterization of the analysed populations suggested probable distinct glacial origin of populations at North and South of the distribution. Furthermore, based on the allelic richness parameter, relict areas could be postulated within each of the identified latitudinal group. Natural hybridisation processes with the close related and sympatric species Nothofagus nervosa were also identified as one of the shaping forces modelling genetic variation patterns of the species. While ancient hybridisation was postulated for the northern watersheds, current hybridisation processes were suggested within the southern ones. Genetic isolation was identified as the main cause promoting the high genetic differentiation found among populations within watersheds